DETECTIN OF VASPIN RS2236242 AND CHEMERIN RS17173608 GENE POLYMORPHSIMS IN A SAMPLE OF OBESE IRAQI POLYCYCTIC OVARY SYNDROME WOMEN - & et al., Jasim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study  was performed to detect assess Vaspin rs2236242  and Chemerin rs17173608 gene  polymorphisms with its association with  susceptibility of  obese PCOS  in  Iraqi women .Blood samples from 100 women with  obese PCOS and 75 healthy control women matched in age and BMI were collected from AL-Yarmouk Teaching hospital during February2018-July 2018 were enrolled in case control study. Tetra amplification refractory mutation system‐polymerase chain reaction (T-ARMS-PCR) was performed to detect the  adipokine SNPs in patients and healthy women  under study. Results demonstrated a significant variations in either genotype distribution and alleles frequencies between the obese PCOS and healthy women regarding vaspin rs2236242 polymorphism. The T allele increased the PCOS risk  in comparison with the A allele which was the protective  against PCOS, as well  clear  positive correlation between rs17173608 SNP of chemerin and susceptibility of PCOS  was identified also, and  The T allele  had related  with elevated PCOS risk  as in comparison to the G allele. Data  from this work determined for the first time a significant association between vaspin and chemerin SNPs  and susceptibility  PCOS  risk in Iraqi  obese women especially T allele .To confirm our findings new studies with large sample size and different ethnicities must be  required.